2011
DOI: 10.1111/j.1365-3083.2011.02531.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Protective Efficacy of a Fusion Protein Vaccine Consisting of Antigen Ag85B and HspX against Mycobacterium tuberculosis Infection in Mice

Abstract: Subunit vaccines have the potential advantage to boost Mycobacterium bovis Bacillus Calmette‐Guérin (BCG)‐primed immunity in adults. However, most candidates are antigens highly expressed in replicating bacilli but not in dormant or persisting bacilli, which exist during Mycobacterium tuberculosis infection. We constructed M. tuberculosis fusion protein Ag85B‐Mpt64190–198‐HspX (AMH) and Ag85B‐Mpt64190–198‐Mtb8.4 (AMM), which consist of Ag85B, the 190–198 peptide of Mpt64, HspX (Rv2031c) and Mtb8.4 (Rv1174c), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 21 publications
(38 reference statements)
0
28
1
Order By: Relevance
“…2). These antibody classes were similarly induced to levels comparable to those induced by other fusion protein constructs, such as the Ag85B-MPT64 190–198 -HspX construct that was used as vaccine booster for BCG in mice or Mtb10.4-HspX (MH) emulsified in DDA–TDM for use as subunit vaccine [26][27].…”
Section: Discussionmentioning
confidence: 83%
“…2). These antibody classes were similarly induced to levels comparable to those induced by other fusion protein constructs, such as the Ag85B-MPT64 190–198 -HspX construct that was used as vaccine booster for BCG in mice or Mtb10.4-HspX (MH) emulsified in DDA–TDM for use as subunit vaccine [26][27].…”
Section: Discussionmentioning
confidence: 83%
“…We found that mice receiving EAMM plus MH had significantly lower bacterial counts in the lungs and spleens compared with EAMM or MH alone. In addition, our previous study also found that fusion protein AMH containing dormancy-related antigen could enhance the effect of AMM [41]. MH and AMH alone did not confer obvious protective effect, but when they were combined with EAMM or AMM they improved the protective effect of EAMM and AMM significantly.…”
Section: Discussionmentioning
confidence: 90%
“…Up to now, our lab has evaluated 9 vaccine candidates based on 9 fusion proteins including AMM [36], Ag85B-MPT64 190-198 -HspX (AMH) [41], EAMM, MH [35], ESAT6-Ag85B, ESAT6-Mtb8.4, Mtb10.4-Ag85B, ESAT6-RpfE, and Ag85B. We found that EAMM provided the most effective protection against M.…”
Section: Discussionmentioning
confidence: 99%
“…10, 11 Until recently, the majority of subunit vaccines were based on antigens expressed during the early stages of M. tuberculosis infection; however, to target protection during latency, several current studies have incorporated the latency-associated antigen, 16-kDa α-crystallin protein (also called HspX, acr and Rv2031c) in heterologous prime-boost strategies using protein HspX subunit vaccines, DNA vaccines expressing HspX and recombinant BCG strains overexpressing HspX. 12, 13, 14, 15 …”
mentioning
confidence: 99%